Clinical practice guideline for the initial pharmacological treatment of lupus nephritis in the Peruvian Social Security (EsSalud) - Ugarte-Gil, Manuel Francisco (2021)
Background: This article summarizes the clinical practice guideline (CPG) for the initial pharmacological treatment of lupus nephritis in the Social Security of Peru (EsSalud). Objective: To provide evidence-based clinical recommendations for initial pharmacological treatment of non-refractory adults with class I to V lupus nephritis in EsSalud. Material and Methods: A guideline development group (GDG) was formed, which included specialist physicians and methodologists, who formulated clinical questions. Systematic searches were conducted for systematic reviews and - when deemed relevant - primary studies in PubMed during 2021. Evidence was selected to answer each of the clinical questions posed. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic working meetings, the GEG used the GRADE methodology to review the evidence and formulate recommendations. The CPG was reviewed by external experts before its approval. Results: The CPG addressed 6 clinical questions, divided into 2 topics: initial treatment of the induction and maintenance phase. Based on these questions, 11 recommendations were formulated (all conditional), 22 points of good clinical practice, and 2 flow charts. Conclusion: Evidence-based recommendations were issued for the management of patients with this pathology.